The diversity of pteridophytes in Siberut National Park, Mentawai Islands, West Sumatra, Indonesia: - - MILDAWATI MILDAWATI; SOBIR SOBIR; SULISTIJORINI SULISTIJORINI; Tatik Chikmawati (Society for Indonesian Biodiversity, 2020)
Abstract. Mildawati, Sobir, Sulistijorini, Chikmawati T. 2020. The diversity of pteridophytes in Siberut National Park, Mentawai Islands, West Sumatra, Indonesia. Biodiversitas 21: 3200-3208. The diversity of Pteridophytes in the Siberut National Park (Siberut NP) Mentawai Islands, West Sumatra, is still very well preserved, but the information is limited. This research aimed to study the divesrity of Pteridophyte species in the Siberut NP in order to provide its taxonomic information using morphological data. The study consisted of exploration to collect plant specimens directly in the field, observation and identification of herbarium specimens in Herbarium Bogoriense and verification using online websites from various sources. A total of 69 species of Pteridophytes classified into 36 genera, and 20 families were recorded in the Siberut NP with Polypodiaceae has the most species diversity with 12 species of 6 genera. As many as 14 species are new records for Siberut Island, i.e. Selaginella involvens (Sw.) Spring (Selaginellaceae), Asplenium simile Blume (Aspleniaceae), Diplazium montanum V.A.V.R (Athyriaceae), Stenochlaena palustris (Burm) Bedd. (Gleichnaceae), Davallia solida (Forst.) Sw. (Davalliaceae), Callistopteris apiifolia (C.Presl) Copel., Crepidomanes humile Bosch (Hymenophyllaceae), Lindsaea carvifolia Kramer, Lindsaea doryphora Kramer, Lindsaea napaea Aldrew. (Lindsaeaceae), Nephrolepis biserrata (Sw.) Schott (Nephrolepidaceae), Ceratopteris thalictroides (L.) Brongn., Haplopteris ensiformis (Sw.) E.H.Crane and Syngramma alismifolia (Pr.) J.Sm. (Pteridaceae). The habitats of Pteridophytes found were mostly terrestrial and epiphytic (34 species each), while aquatic habitat was only found to one species. The results of this study will serve as baseline information of the plant diversity in the Siberut NP that can be used as the reference for future studies on Pteridophytes and to develop their conservation strategy in the region.